Morfologi Serbuk Sari Familia Poacea di Kampus Universitas Syiah Kuala Banda Aceh - Teuku Fakhrizal (Biotik, 2015)
The title of the research was "The morphology of pollen of Familia Poaceae at Syiah Kuala University in Banda Aceh". The purpose of this study was to know the morphology of Poaceae allergenic. The microscopic pollen preparat was made by acetolysis method. The data were collected by using descriptive methods and photos. Pollen microscopic preparat was made by acetolysis method. The data were collected by using descriptive method and picture. The parameters used in this research were unit, shape, aperture, sculpture, and allergenic types of the pollen. The result showed that there were 30 species of grass from familia poaceae. The pollen unit was all monads, its shape was subspheroidal, the size was varied magna, media, and minute +, its apertures were tricolpage and monoporate. Its sculpture has psilate, acabrate, and bverrucate. Looking from its sculptur, the pollen was allergenic.